Documenting Best Practices: Towards a Framework for Expanding Local Governance - Peter.M.Raj (KILA Journal of Local Governance, 2013)
Thanks to the strong devolution process in Kerala, many of the Local Governments in the state are coming out with innovative practices. These best practices need to be documented for the purpose of peer learning and adaptation strategy. KILA has been continuously documenting the best practices of Local Governments so as to better use for peer learning programmes entitled “Panchayat to Panchayat”. This paper deals with a methodology framework for documenting the best practices and provides selection criteria for identifying best practices as well.